Análise da eficiência relativa das Empresas Juniores no Brasil - Hercos Junior, José Braz (2014)
The "entrepreneurship", "knowledge" and "innovation" are differential for competitiveness. In this context the Higher Education Institutions act as a diffusion agent. The Student Enterprises constitute a mechanism that assists those Institutions to develop the attributes listed. This research objective is to identify and analyze the factors that determine the management efficiency in Student Enterprises. The research scientific contributions are the adoption of methodological techniques and description of aspects such as knowledge generation, Student Enterprises efficiency and their determinant management factors. The following methodological techniques were applied to Junior Brazil (Student Enterprises Brazilian Confederation) data: a) nonparametric Data Envelopment Analysis (DEA) to evaluate Student Enterprises relative technical efficiency; b) "regression analysis" and "analysis of variance", to identify management factors that explain the efficiency differences between Student Enterprises; and, c) descriptive statistics to assess Student Enterprises from other perspectives. The research sample is composed by fifty-two (52) Student Enterprises from Social Sciences courses affiliated to Junior Brazil. Empirical results indicate that Student Enterprises have characteristics in common, such as: a) the Higher Education Institutions support; b) the training and consulting services as the main activity; c) the most of customers being individuals, micro and small enterprises; d) the Student Enterprises members acting without remuneration; e) knowledge being main variable used in training activities and consultancy services provided. Using Data Envelopment Analysis (DEA), it was found that most of Student Enterprises are far from achieving efficiency. In order to generate subsidies that favor effectiveness were identified and analyzed the management factors that explain the differences in efficiency between the Student Enterprises, namely "participation in events", "ability to negotiate", "market time" "strategic actions carried" and "strategic indicators within the target" .